An ecological approach to understanding university English teachers’ professional agency in implementing formative assessment - Jiang, Yuhong; Li, Jia; Wang, Qiang (Frontiers in Psychology, 2022)
Teachers’ professional agency, as the sub-realm of Language Teacher Psychology (LTP), has also gained much attention from educational executors and teachers for better discerning teacher professional development and teaching effectiveness to ensure the quality of language teaching. International literature concerning teachers’ professional agency has perceived a shift from knowledge training to vocational development in relation to teachers’ experience in decision making. Yet little research so far has scrutinized this specific issue involved in Chinese university settings and the real picture of teacher agency needs further exploration. Besides, the multidimensional and complex nature of agency identifies the overwhelming research work in understanding its contents in detail based on the previous perspectives from individual, society and time. To this end, the ecological understanding of professional agency reframed the theoretical basis of this study, prone to explore how teachers’ experience could be examined in relation to individual capacity, resource, structural and contextual variables. The study was conducted in the Chinese university settings in response to the research gap in understanding professional agency. Quantitative and qualitative data from questionnaire, interview and classroom observation with 116 university teachers in China demonstrated that the enactment of professional agency banked on the interplay between temporal contexts, teacher capacity, and beliefs, especially in the instructional community. The findings revealed that university teachers in the different course of career development manifested variably in exercising their professional agency in relation to adapting or subjecting to existing teaching concepts, methods, or approaches. Mounting evidence revealed some enablers and constraints in relation to formative assessment, time impact, classroom interaction and school culture. Teachers in the different course of career development manifested variably in exercising their professional agency in relation to adapting or subjecting to existing teaching concepts, methods, or approaches. By virtue of emphasizing the interaction between individuals’ ability and their engagement with professional environment, the findings provide insights into theoretical implications associated with ecological theory and enhance the practical discussion on promoting professional development for university novice, mid-career and veteran English teachers.